The Effectiviness Of The “BANGDAT” Pbl-Based Learning Materials For Improving Elementary School Students’ Understanding Of Mathematical Concepts - Ramadhan, Fitra; Mufliva, Rosiana; Azhara Suherman, Silvi Fatimah; Riyadi, Diki; Arrasyid, Muhammad Keisar (Current Issues on Elementary Education Journal, 2025)
study aims to examine the effectiveness of teaching materials ‘Misi BangDat’ based on Problem-Based Learning (PBL) in improving the understanding of mathematical concepts of elementary school students on the material of flat buildings. The research design used pre-experimental method with one-group pretest-posttest. The research sample consisted of 24 grade II students in one of the elementary schools in West Bandung Regency. The results showed an increase in the average score of students' understanding of mathematical concepts from 57.29 (pretest) to 82.29 (posttest). N-Gain analysis showed a score of 80.87%, which is in the high category, proving that this teaching material is effective. The implementation of PBL-based teaching materials helps students understand concepts interactively and contextually, improve critical thinking skills, and facilitate understanding of abstract mathematics material. This study recommends the use of ‘Misi BangDat’ teaching materials as an innovative solution to improve mathematics learning at the primary school level.